Laryngeal Framework Surgical Anatomy: A Radiological Study - GÜNDOĞMUŞ, CEMAL AYDIN; OYSU, ÇAĞATAY; ÜÇKUYULU, ESİN İREM; ENVER, NECATİ (Mosby Inc., 2021)
Purpose: Awareness of variations in laryngeal anatomy among different age and gender groups is crucial during laryngeal framework surgery. The aim of this study is to demonstrate the relationship between gender and laryngeal radiologic morphometrics among different age groups and the applicability of important anatomical landmarks of laryngeal surgery. Methods: Laryngeal images of 180 adult patients older than 18 years of age were obtained by computed tomography and assessed. A total of 11 measurements of important laryngeal landmarks were taken from the patients’ computed tomography images. Results were subgrouped according to gender and age, and these groups were compared for each measurement. Results: The majority of laryngeal measurements obtained in the study were higher in males than females, with the exception of the interlaminar angle. The mean interlaminar angle value was 88.27°± 14.99 for males and 103.04°± 14.81 for females (P <0.005). The distance from the anterior commissure to the inferior border of the thyroid cartilage was 10.46 ± 2.5 mm for males and 7.72 ± 1.9 mm for females. The anterior commissure locates slightly higher than the midpoint of the distance from the thyroid notch to the thyroid inferior border. The shortest distance between the muscular process of the arytenoid cartilage and the thyroid cartilage was found to be 9.60 ± 3.47 mm for males and 7.72 ± 2.33 mm for females (P <0.001). Conclusion: Observation of obvious diversities in the size and distance of the important laryngeal structures between the gender groups is an important factor to be considered for successful laryngeal framework surgery. Also, using the midpoint of the thyroid cartilage as a landmark for anterior commissure is a practical method during surgery, especially for thyroplasty. © 2021 The Voice Foundation
Keywords: Laryngeal framework—Larynx—Morphometric measurement—Surgical anatomy—Radiology—Thyroplasty—Anterior commissure